Perencanaan Konstruksi Perkuatan Tebing Sungai Krueng Teunom - Alfiansyah, Oki; Syahputra, Ichsan; Ridha, Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The purpose of this study was to determine the Safety Factor value at the research location before being reinforced with sheet piles using Plaxis 2d Software and to plan safe sheet piles and reinforcement dimensions and to analyze the forces that work and determine the safety factor value in sheet pile construction. The results of this analysis can be used as a basis for planning reinforcement of the Krueng Teunom river bank. Slope stability analysis using Plaxis 2D at the review location was carried out by creating 2 models, namely modeling extreme normal conditions or the highest river water level, The safety factor figure on the review slope using Plaxis 2D under normal conditions has an SF of 1.446 before being reinforced and 2.373 after being reinforced. extreme conditions have an SF of 1.081 before being reinforced and 1.811 after being reinforced. The land subsidence figure due to consolidation on the normal condition review slope has a figure of 0.03 m before being reinforced and 0.02 m after being reinforced. extreme conditions have a figure of 0.08 m before being reinforced and 0.07 m after being reinforced. The planned slope reinforcement is a cantilever retaining wall with total wall height (H) dimensions of 4.50 m, total width (B) of 2.70 m and embankment slope angle of 10°. With flexural reinforcement D19-200 mm, shrinkage ∅10-75 mm, heel-toel section D19-150 mm and horizontal reinforcement tread ∅10-75 mm.